Transverse impact analysis of double-layered graphene sheets on an elastic foundation. (March 2018) - Natsuki, Toshiaki; Natsuki, Jun
Abstract: In using graphene sheets (GSs) to design nanoscale devices or nanostructure elements, it is very important to understand the properties of these elements against various mechanical loading conditions. The aim of this study is to investigate the impact response of double layer graphene sheets (DLGSs) on elastic foundations when they are subjected to low-velocity impact by nanoparticles. The analytical model is based on general continuum mechanics theory, which considers that a layer stack of two individual GSs is bound together by van der Waals (vdW) forces, and the interaction of DLGSs embedded to elastic foundations is modeled based on the Winkler model. The result shows that elastic foundation materials have a significant effect on the impact characteristics of GSs. The impact response of GSs subjected to nanomass has exceedingly short times with picoseconds order. This investigation may be helpful in engineering design of using GSs as nanostructure elements for nanoelectromechanical system (NEMS).